Optimization of the Reversible Lane considering the Relationship between Traffic Capacity and Number of Lanes - Jianrong Cai; Jianhui Wu; Zhixue Li; Qiong Long; Zhaoming Zhou; Jie Yu; Xiangjun Jiang (Journal of Advanced Transportation)
To make full use of road resources, improve the operation efficiency of the road network system, and alleviate the coexistence between traffic congestion and road resources idle caused by the traffic tidal phenomenon, the impact of the number of lanes on traffic capacity is examined, and the mixed-integer bilevel programming model for reversible lane optimization is established with the aim to minimalize the total travel time of the system. Taking a test road network as an example, the influence of the reversible lane optimization on characteristic values of sections, the route travel time between OD pairs, and the total time of the system are analyzed. The results indicate that the reversible lane optimization can make full use of the idle road resources and make the road network structure match the travel demands better, and the system index after the reversible lane optimization is obviously better than the original system index.